Moabite women, Transjordanian women, and incest and exogamy: The gendered dimensions of boundaries in the Hebrew Bible - Sabo, Peter J (Journal for the study of the Old Testament, 2020)
Building on the work of David Jobling (who suggests there is a structural coding of the Cisjordan as male and the Transjordan as female) and Rachel Havrelock (who suggests the Transjordan and Moab are places of gender deviancy), this article explores issues of geographical, ethnic, and gender identity in stories of Moabite and Transjordanian women. Particular attention is given to the twin tropes of incest and exogamy and how this relates to the pattern of anxiety and lost identity in the Transjordan. Analysis begins with the story of Lot’s daughters, who serve as archetypal and paradigmatic Moabite women, and moves on to include the Moabite women in Numbers 25, Zelophehad’s daughters, Jephthah’s daughter, and Ruth.